Zhenwu decoction ameliorates cardiac hypertrophy through activating sGC (soluble guanylate cyclase) - cGMP (cyclic guanosine monophosphate) - PKG (protein kinase G) pathway. (10th January 2023) - Chen, Liqian; Zhou, Xinghong; Deng, Yijian; Yang, Ying; Chen, Xiaohu; Chen, Qinghong; Liu, Yanyan; Fu, Xiuqiong; Kwan, Hiu Yee; You, Yanting; Jin, Wen; Zhao, Xiaoshan
Abstract: Ethnopharmacological relevance: Zhenwu Decoction (ZWD) is a traditional Chinese medicine (TCM) formula which has wide scope of indications related to Yang deficiency and dampness retention in TCM syndrome. Cardiac hypertrophy can induce similar symptoms and signs to the clinical features of Yang deficiency and dampness retention syndrome. ZWD can increase the left ventricular ejection fraction, reduce cardiac hypertrophy of patients with chronic heart failure. However, its underlying pharmacological mechanism remains unclear. Aim of the study: The study aimed to confirm the protective effects of ZWD on cardiac hypertrophy and explore the underlying mechanisms. Materials and methods: The potential targets and pathways of ZWD in cardiac hypertrophy were highlighted by network pharmacology and validated by mechanistic and functional studies. Results: Our network pharmacology analysis suggests that the protective effects of ZWD on cardiac hypertrophy are related to cyclic guanosine monophosphate (cGMP) - protein kinase G (PKG) pathway. Subsequent animal studies showed that ZWD significantly ameliorated cardiac function decline, cardiac hypertrophy, cardiac fibrosis and cardiomyocyte apoptosis. To explore the underlying mechanisms of action, we performed Western blotting, immunohistochemical analysis, and detection of inflammatory response and oxidative stress. Our results showed that ZWD activated the soluble guanylate cyclase (sGC) - cGMP - PKG signaling pathway. The sGC inhibitor ODQ that blocks the sGC-cGMP-PKG signaling pathway in zebrafish abolished the protective effects of ZWD, suggesting sGC-cGMP-PKG is the main signaling pathway mediates the protective effect of ZWD in cardiac hypertrophy. In addition, three major ingredients from ZWD, poricoic acid C, hederagenin and dehydrotumulosic acid, showed a high binding energy with prototype sGC. Conclusion: ZWD reduces oxidative stress and inflammation and exerts cardioprotective effects by activating the sGC-cGMP-PKG signaling pathway. Graphical abstract: Image 1 Highlights: Zhenwu Decoction (ZWD) exhibited significant therapeutic effects on cardiac hypertrophy. ZWD restored the sGC-cGMP-PKG signaling pathway suppressed by cardiac hypertrophy. Inhibition of the sGC-cGMP-PKG signaling pathway abolished the protective effect of ZWD on cardiac hypertrophy.